Inability of 7,8 – Dihydroxy-4- Methylcoumarin antioxidant activity, to prolong longevity and to protect against stress in Caenorhabditis Elegans worms - Pereira, Gustavo José de Sá; Cardoso, Ronan Martins; Fernandes, Célio Junior da Costa; Ferreira, Vanuzia Rodrigues Fernandes; Cardoso, Maria das Graças; Thomasi, Sérgio Scherrer; Moura, Rodrigo Ferreira de (Open Science Journal, 2023)
Despite an increase in life expectancy, it is known that this factor is not necessarily accompanied by a better quality of life, which reflects in longevity. Aspects related to metabolic stress to which cells are subjected can modulate this process, which can lead to various pathologies. Coumarins are secondary metabolites found in several plants, such as guaco, and are part of the polyphenol family capable of producing up to 1300 derivatives, with potential effects against metabolic stress, in addition to being used in the cosmetics industry with the objective of improving fragrance of products. Therefore, it seems necessary to seek to elucidate molecular mechanisms that can regulate this aging process, which can be associated with the gradual loss of physiological functions of cells and tissues, increasing the number of cells in senescence that may be related to increased oxidative stress. PURPOSE: the aim of this study was to identify the influence of the use of the coumarin synthetic compound 7,8-Dihydroxy-4-methylcoumarin (DHMC) on longevity and resistance to different types of stress in vivo. METHODS: free radical scavenging (DPPH) analyzes were performed for the compound, longevity, and stress tests (H2O2, NaCl, Heat) for C. elegans worms. RESULTS: in the first analysis, the compound showed 92% of antioxidant activity already in small concentrations (25ug/ml) through DPPH analysis. In the following tests DHMC did not show antibacterial responses against Escherichia coli, and Caenorhabditis elegans worms did not show stress reduction or significant improvement in longevity with the use of the compound. CONCLUSION: therefore, the DHMC compound expresses a high antioxidant activity and presents several study potentials. However, it has no biological effects in protecting against stress or contributing to longevity in C. elegans worms